How Does Stomatal Density and Residual Transpiration Contribute to Osmotic Stress Tolerance? - Md. Hasanuzzaman; Meixue Zhou; Sergey Shabala (Plants, 2023)
Osmotic stress that is induced by salinity and drought affects plant growth and development, resulting in significant losses to global crop production. Consequently, there is a strong need to develop stress-tolerant crops with a higher water use efficiency through breeding programs. Water use efficiency could be improved by decreasing stomatal transpiration without causing a reduction in CO2 uptake under osmotic stress conditions. The genetic manipulation of stomatal density could be one of the most promising strategies for breeders to achieve this goal. On the other hand, a substantial amount of water loss occurs across the cuticle without any contribution to carbon gain when the stomata are closed and under osmotic stress. The minimization of cuticular (otherwise known as residual) transpiration also determines the fitness and survival capacity of the plant under the conditions of a water deficit. The deposition of cuticular wax on the leaf epidermis acts as a limiting barrier for residual transpiration. However, the causal relationship between the frequency of stomatal density and plant osmotic stress tolerance and the link between residual transpiration and cuticular wax is not always straightforward, with controversial reports available in the literature. In this review, we focus on these controversies and explore the potential physiological and molecular aspects of controlling stomatal and residual transpiration water loss for improving water use efficiency under osmotic stress conditions via a comparative analysis of the performance of domesticated crops and their wild relatives.